The Role of Forward-Looking Disclosure in the Relationship of R&D Expenditure and Firm Value: Testing Agency and Signaling Theories - Presccilia Angel; Widiastuti Harjanti (SHS Web of Conferences)
This study aims to examine the effect of Research and Development (R&D) expenditure on firm value with forward-looking disclosure as a moderating variable. This study used a sample of 124 manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2019 2022. Data analysis used panel data regression. The results showed that R&D expenditure has a positive effect on firm value. However, this study found that forward-looking disclosure does not moderate the relationship between R&D expenditure and firm value.